BIODEGRADATION OF POLYURETAN RESULTS OF SYNTHESIS OF SOYBEAN OIL, GLYCOLOLY POLYOKYLETHLES, AND METHYLES-4,4'-DIFENILDIISOSIANAT - Eli Rohaeti; Senam Senam (Jurnal Penelitian Saintek, 2010)
The objective of research were to synthesize polyurethane from  soybean oil, P EG400 and MDI,  to  determine  the  cross  linking,  and  to  learn  the  influence  of  incubation  times toward  degradability  of polyurethane.   Polyurethane   was  synthesized from  soybean  oil and oxydated soybean oil at room temperature followed  by curing for 10 hours at 70 DC,and  than  at  100 "c for 3 hours.  The synthesis  was  conducted  with  mass  compositionSBOI  OSBO  : P EG400  : MDI = 1 : 2  : 3.   Biodegradation   was  conducted  by usingmicroorganism   in  an  actived  sludge   of  malka  medium   at  37°C.    The  variation   of incubation  times were 5, 10, 15, 20, 25, and 30 days, respectively  with changes of media every 5 days.  Characterizations   of polyurethane   were functional   groups,  cross  linking, mass loss and biodegradability.  The oxydated soybean  oil has increased intensity of -OR functional   group,  hydroxyl  number,  density,  melting  and  boiling point,  otherwise  the refraction    index   has   decreased.    The   synthesized   polyurethane    has   characteristic absorption  of urethane functional  group and cross link. The increasing of incubation time can  decrease  biodegradability   of polyurethane.   The mass  loss    of polyurethane  from SBO-PEG400-MDI   has  the higher.  Biodegradation   can disappear  urethane  group  and decrease crystallinity  of polyurethane. Key words: biodegradation,  mass loss, crystallinity, polyurethane